2014
DOI: 10.1111/jfbc.12086
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Alkaline Electrolyzed Water as an Inhibitor of Enzymatic Browning in Red Delicious Apples

Abstract: Polyphenol oxidase (PPO) activity, hue angle, chroma and browning index (BI) of alkaline electrolyzed (EO) water‐treated apples were compared with apples treated with other anti‐browning agents (ascorbic acid, citric acid and sodium metabisulfite). Alkaline EO water was shown to reduce PPO activity by about 66%. Apples treated in alkaline EO water for 5 min had less reduction on hue angle (97.0–91.1) after 24‐h storage than apples treated with deionized water (93.4–83.7) and hence less brown. Apples treated in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 36 publications
1
3
0
Order By: Relevance
“…Therefore, we can infer that there is less pigmentation in potatoes treated with SMB, due to its decolorizing and whitening property (Vanier et al , 2015). Similar results were reported by Kim and Hung (2014), with different combinations of solutions on the enzymatic browning of apples and showed that treatments containing SMB resulted in apples with lower values of C*.…”
Section: Resultssupporting
confidence: 88%
“…Therefore, we can infer that there is less pigmentation in potatoes treated with SMB, due to its decolorizing and whitening property (Vanier et al , 2015). Similar results were reported by Kim and Hung (2014), with different combinations of solutions on the enzymatic browning of apples and showed that treatments containing SMB resulted in apples with lower values of C*.…”
Section: Resultssupporting
confidence: 88%
“…Hung et al, (2010) observed no significant (p > .05) effect of EW treatment on the color parameters of strawberry fruit stored at 4℃ for 21 days. On the contrary, Kim and Hung (2014) stated the significant effects of EW on apple (cv. Red Delicious) during storage.…”
Section: Nectarine Fruit Peel Colormentioning
confidence: 95%
“…Both treatments aid in removing chemical residues from the fruit and have a strong bactericidal effect. Additionally, electrolytic water acts as a scavenger of free radicals (Kim & Hung, 2014 ). Ahmed et al developed new films using Ditriterpenoids and Secomeliacins isolated from Melia azedarach (Dharek) and Azadirachta indica plants.…”
Section: Opportunities and Challenges For The Utility Of Applesmentioning
confidence: 99%